RELATIONSHIP BETWEEN INTERLEUKIN-6 LEVELS AND PRURITIC EVENTS IN PATIENTS WITH CHRONIC KIDNEY DISEASE UNDERGOING REGULAR HEMODIALYSIS - Dewi Fuji Lestari, Riri A. Muzasti & Syafrizal Nasution (International Journal of Research Science and Management, 2019)
Introduction: Patients with chronic kidney disease (CKD) who undergo hemodialysis often have several complaints and pruritus is estimated to occur in 20% - 90% of these patients. Inflammation is thought to play an important role in pruritus in hemodialysis patients. Among a number of pro-inflammatory cytokines, research shows that IL-6 is the central regulator of the inflammatory process, and is found in dermal nerve fibers. Method: This is an analytical study with cross-sectional design to determine the relationship between IL-6 levels and the incidence of pruritus in CKD patients undergoing regular hemodialysis. Patients were asked to fill out the Pauli-Magnus questionnaire and a serum level of IL-6 laboratory test was then conducted. After the data was collected, data processing and analysis were conducted. Results: Of 100 patients, it was found that IL-6 levels were statistically associated with the incidence of pruritus (0.001). Conclusion: From this study it can be concluded that there was a relationship between IL-6 levels and the incidence of pruritus in CKD patients undergoing regular hemodialysis